PENGEMBANGAN E-BOOK BAHASA INGGRIS UNTUK SISWA SMA - Evrianti Evrianti; Nina Kurniah (DIADIK, 2021)
The aims of this study to: Create an e-book on the subject of English XI grade at Vocational High School Number 3 Pagar Alam City which is feasible to improve student achievement. In this study uses a development design (Research and Development). The subjects of this study are students of Science Class XI of Senior High School Number 3 Pagar City. The data collection techniques used in the study were (1) Assessment sheets for product validation and to describe student responses. (2) The results of student tests to analyze the increase in student achievement. The data analysis used mean and t-test. The instrument of this study uses a Linkert scale. The conclusions of this research are; (1) The development of this English E-Book is feasible to improve student achievement in learning English according to the validation of material experts and the validation of media experts obtained an average score is 3.85 with “Very Eligible” criteria. (2) The development of this English e-book can improve student learning outcomes based on the results of a wide-scale trial trial of class XI MIPA students of SMA Negeri 3 Pagar Alam in English subjects obtained based on the results of a wide- scale trial trial of class XI MIPA students of SMA Negeri 3 Pagar Alam in English subjects, the results obtained from the study it can be concluded that the developed English ebook can significantly improve student achievement in English subjects